Evaluation of the effectiveness of allogeneic tendon graft sterilization with supercritical carbon dioxide - A. A. Budaev; N. V. Borovkova; A. M. Fayn; A. Yu. Nikolaev; M. S. Makarov; M. V. Storozheva; K. I. Skuratovskaya; A. Yu. Vaza; I. V. Fomicheva; T. V. Chernen'kaya; A. А. Kanibolotskiy (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
Structural and functional properties of the human tendon tissue complicate process of tendon-based grafts preserving. In the process of preservation, it is necessary to maintain mechanical and functional parameters of the tendon tissue as well as to provide sterility and biological safety of the graft. One could conclude effectiveness of techniques, combining tendon conservation at low temperatures and sterilization with the supercritical carbon dioxide.Aim of work: to find optimal conditions for allogeneic tendon grafts sterilization with supercritical carbon dioxide.Materials and methods. Allogeneic tendons were prepared from the tissue donors, following the rules of asepsis and antisepsis. After quarantine and confirmation of the absence of blood-borne infections the tendon grafts were divided into 3 groups: in the control group the tendons were not subjected to cryopreservation and sterilization procedures; in 2 experimental groups tendons were treated with a cryoprotector 10 % dimethyl sulfoxide (DMSO) solution and sterilized with supercritical carbon dioxide with slow gas discharge (group 2) or with fast gas discharge (group 3); the duration of sterilization in both groups varied from 1 to 12 hours. The toxicity of the grafts was assessed in human mesenchymal multipotent stromal cells (MMSC) culture on the 3rd and 7th days. The sterility of the grafts was confirmed on the 7th and 14th day by bacteriological culture on thioglycol medium and Saburo broth. Mechanical tests were performed on testing machine LLOYD Instruments LR5K Plus with the tensile speed 5 mm/min.Results. Histological analysis showed, that in the group with slow gas discharge collagen fibers retained their integrity and topography and contained only local minor tears; in all terms of treatment, the tendon grafts were sterile and nontoxic. On the contrary, in the group with fast gas discharge there was marked damage of the collagen fibers and growth of bacterial and fungal flora was observed in the culture. The grafts of the control group and the group, where sterilization with supercritical carbon dioxide was performed with slow gas discharge for 1-12 hours, were used to evaluate mechanical characteristics. In the preserved tendons the stiffness and ultimate strain did not significantly differ from the similar values in the control (p > 0.05), on the contrary, the level of ultimate strain in all experimental specimens was significantly reduced by 1.5-2.1 times comparing to the control. Young's modulus and load at rupture in the control grafts and grafts, sterilized for 1 hour, had similar values, whereas in grafts, sterilized from 3 to 12 hours, these parameters were 1.4-2.1 times lower (p < 0.05).Conclusions. The suggested technique of tendon preservation, using cryoprotector DMSO and sterilization with the supercritical carbon dioxide, allows to obtain sterile and non-toxic grafts. The structure of cells and fibers of the preserved tendons did not significantly disturbed. For supercritical carbon dioxide sterilization of tendon grafts the most optimal processing time is 1 hour.